SOCIAL MEDIA, ARCHAEOLOGICAL NEWS, AND CULTURAL RESOURCE MANAGEMENT: THE CASE OF MOYANG.CO - Pratama Dharma Surya (Kalyanamitra: Journal of Archaeological Resource Management, 2026)
This article critically examines the role of digital heritage media in framing recent archaeological discoveries and government heritage policies within the framework of Cultural Resource Management (CRM). Using Moyang.co, an Indonesian Instagram-based heritage media platform, as a case study, this research analyzes how news related to new archaeological findings, research outcomes, and state interventions are communicated, questioned, and negotiated in the public sphere. Employing qualitative content analysis of selected Moyang.co posts published between 2024 and 2025, this study applies CRM perspectives emphasizing values-based management, public archaeology, and participatory heritage governance. The results demonstrate that Moyang.co functions not merely as an information outlet, but as a critical mediator that connects archaeological discovery with issues of management responsibility, policy transparency, and stakeholder inclusion. By consistently situating discoveries within broader governance and conservation contexts, Moyang.co challenges state-centered heritage narratives and highlights gaps between policy formulation and on-the-ground management. This article argues that digital heritage media has become an integral yet under-recognized component of contemporary CRM, particularly in contexts where archaeological discoveries are rapidly publicized while management responses remain slow, contested, or opaque.